2022
DOI: 10.1111/soru.12413
|View full text |Cite
|
Sign up to set email alerts
|

Wellbeing, environmental sustainability and profitability: Including plurality of logics in participatory extension programmes for enhanced farmer resilience

Abstract: Environmental sustainability and economic challenges are requiring significant change in the agricultural sector, and this is driving an increased focus on farmer and farm business resilience. Participatory extension programmes (PEPs) are a well‐known approach for supporting farmer change. The objective of this article is to explore how a PEP based on peer‐to‐peer learning can support farmers in increasing resilience. Our study examines the interaction of wellbeing, environmental change and profitability throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The study adds to the limited literature on the connection between educators and students in mental health workshops in a rural context (Knook et al, 2022b; Stanley-Clarke, 2019). While the findings cannot be generalised due to sample selection and size, they add to learning and are relevant to the delivery of mental health wellbeing programmes to agricultural students by stressing the importance of relationships and building connection.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The study adds to the limited literature on the connection between educators and students in mental health workshops in a rural context (Knook et al, 2022b; Stanley-Clarke, 2019). While the findings cannot be generalised due to sample selection and size, they add to learning and are relevant to the delivery of mental health wellbeing programmes to agricultural students by stressing the importance of relationships and building connection.…”
Section: Discussionmentioning
confidence: 96%
“…One way of building wellbeing resilience is by introducing those working and living in farms to aspects of wellbeing via extension and education programmes (Knook et al, 2022b). These programmes can be helpful in conveying mental health concepts to those who come from rural communities, such as university students (Stallman and Shochet, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final article by Knook et al. (2023) furthers our evaluation of support interventions for farmer wellbeing. The authors examine profitability, environmental and wellbeing change amongst farmers participating in a participatory extension programme (PEP) in Aotearoa‐New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative agriculture extension systems studies indicate that aspects such as formal and technical knowledge, governance, polycentric management structures, social capital, human capital, physical capital, natural capital, and social capital are linked to farmer resilience (Bhowmik et al 2021;Kliem, 2022;Meuwissen et al 2019). Other qualitative studies also identified the agriculture extension factors that contribute to building farmer resilience (Hunt et al 2011;Knook et al 2023), however, the magnitude of the relationship is yet unknown. Studies on the effect of agricultural policies on resilience also revealed the influence of agricultural policies on farming systems' resilience (Buitenhuis et al 2020;Thorsøe et al 2020).…”
Section: Introductionmentioning
confidence: 99%